Soil fertility status and land suitability evaluation for rice crops on former shrimp ponds: Soil fertility status and land evaluation assessment - Ripaldi S. Sabudu; Moh Zulfajrin; Mihwan Sataral; Hidayat Arismunandar Katili; Herwin Yatim (Faculty of Agriculture, Tompotika Luwuk University, 2021)
Undertaking suitable land, including former shrimp ponds for rice, is required to cope with future rice shortages. The purpose of this study was to identify the soil morphology and physicochemical properties, determine soil fertility status and assess irrigated rice suitability of ex-shrimp ponds. Soil morpho-physicochemical properties such as soil color, structure, texture, pH, organic-C, P2O5, K2O, base saturation, and cation exchange capacity were determined. The resulting data was then matched into the criteria for BSCR and SLAN/CCDS, five major soil fertility criteria, and ICALRRD land suitability. Soil physiographical, morphological, and physicochemical analysis suggested that the soil developed from the alluvial site of calcareous-marl parent material located at saturated backswamp, then permanently drained. ESP, SAR, and salinity values were detected relatively lower than saline, sodic, and saline-sodic soil. The entire cations fell below BCSR ideal ratios, whereas all exchangeable K were detected below the CCDS/SLAN thresholds. Actual suitability for land units of A, B, and C were S3-rc,na, S3-na and S3-rc,nr,na,eh, respectively. The improvement such as fertilization, amelioration, slope flattening/cut-filling, and irrigation management increases all land units to S1. This study pinpointed the importance of former shrimp pond soil to provide suitable land for rice crop cultivation. Also, encouraging further research to identify the origin of alluvial parent material from the soil at the study site